Effects Rahn, Ijaroh, Customer Satisfaction Through Quality of Service in. PT. Sharia Rural Bank Syarikat Madani - Wibisono, Chablullah; Budi Harto, Rahmad (International Journal of Engineering and Technology, 2018)
Community desire of a product needs the companion for business credit financing, disposal venture capital partners for micro s and macro businesses and banking sector needs to increase every year, so the role of the strategic investment partner is so decisive.Â As the products business development, Since 1991 Islamic banking system has served the public with "Syariah" products. To achieve these objectives, the role of the corporate world become extremely important to give influences in society economy, so better services to achieve customer satisfaction in banking area is needed.The data in this research was conducted by spreading some questionnaires and taking the entire sample of 150 respondents of PT. SRB SayrikatMadani, and then the Data were tested by using Path analysis. The test results showed that the variable of Rhan (X1) Customer Satisfaction (Y) through Quality Services (X3) has path coefficient value 0554 t-count = 0223 while t-table 1661 (Î± = 0.05) and 2367 (Î± = 0, 01). It showed that the value of t-count <t table, it can be concluded that the path coefficient is not significant. Ijaroh (X2) The customer Satisfaction (Y) through Services Quality (X3) has path coefficient 0.315 t-count = 0.016 while t-table 1661 (Î± = 0.05) and 2367 (Î± = 0.01). in this case, t count <t table, it can be concluded that the path coefficient is not significant.Â Â